Plant defensive responses to insect eggs are inducible by general egg-associated elicitors - Vivien Lortzing; Georgios Valsamakis; Friederike Jantzen; Janik Hundacker; Luis R. Paniagua Voirol; Fabian Schumacher; Burkhard Kleuser; Monika Hilker (Scientific Reports, 2024)
Abstract Egg deposition by herbivorous insects is well known to elicit defensive plant responses. Our study aimed to elucidate the insect and plant species specificity of these responses. To study the insect species specificity, we treated Arabidopsis thaliana with egg extracts and egg-associated secretions of a sawfly (Diprion pini), a beetle (Xanthogaleruca luteola) and a butterfly (Pieris brassicae). All egg extracts elicited salicylic acid (SA) accumulation in the plant, and all secretions induced expression of plant genes known to be responsive to the butterfly eggs, among them Pathogenesis-Related (PR) genes. All secretions contained phosphatidylcholine derivatives, known elicitors of SA accumulation and PR gene expression in Arabidopsis. The sawfly egg extract did not induce plant camalexin levels, while the other extracts did. Our studies on the plant species specificity revealed that Solanum dulcamara and Ulmus minor responded with SA accumulation and cell death to P. brassicae eggs, i.e. responses also known for A. thaliana. However, the butterfly eggs induced neoplasms only in S. dulcamara. Our results provide evidence for general, phosphatidylcholine-based, egg-associated elicitors of plant responses and for conserved plant core responses to eggs, but also point to plant and insect species-specific traits in plant–insect egg interactions.